Obstructive voiding symptoms in female patients with overactive bladder syndrome. (November 2019) - Zilberlicht, Ariel; Haya, Nir; Goldschmidt, Eyal; Feferkorn, Ido; Lavie, Ofer; Abramov, Yoram
Abstract: Objectives: To characterize obstructive voiding symptoms (OVS) in patients with overactive bladder (OAB) and normal postvoid residual volume (PVR) and assess their impact on patients' quality of life (QoL) and sexual function. Study design: Patients with OAB and normal PVR who visited our urogynecologic clinic between November 2016 and June 2017 were asked to fill a questionnaire comprising of 14 statements regarding Obstructive VOiding Symptoms (the OVOS questionnaire). Patients additionaly completed the UDI-6 and IIQ-7 questionnaires. Statistical analysis was performed to determine the prevalence of each OVS and its correlation with the UDI-6 and IIQ-7 scores. Results: Thirty-eight women enrolled in this study. The OVOS questionnaire was found to have good reliability (Cronbach's alpha = 0.75) and construct validity. Thirty-six (95%) women reported having at least one, while 34 (90%) had at least two, and 31 (82%) had at least three OVS. The statement: `I feel that I am unable to empty my bladder completely` significantly correlated with the sense of frustration (r = 0.44, p = 0.006), as well as with the overall negative impact of urinary incontinence on QoL (r = 0.36, p = 0.03). The statement: `I feel a sensation of fullness immediately after I empty my bladder` significantly correlated with the total impact of urinary incontinence on sexual function (r = 0.42, p = 0.031). Conclusions: Most patients with OAB and normal PVR complain of OVS which may increase the burden on their QoL and sexual function. Some OVS correlate with various segments of the UDI-6 and IIQ-7 questionnaires, suggesting that storage and OVS may share common pathophysiological mechanisms.